2019
DOI: 10.1016/j.ijhydene.2018.02.164
|View full text |Cite
|
Sign up to set email alerts
|

Syngas production from dry methane reforming over yttrium-promoted nickel-KIT-6 catalysts

Abstract: Dry reforming of methane was studied over Ni,Y-promoted KIT-6 ordered mesoporous silicas, prepared by incipient impregnation (nickel content 12 wt.%, yttrium content of 4 wt.%, 8 wt.% or 12 wt.%). The catalysts were characterized by XRF, FT-IR, TGA/DSC-MS, N2-adsorption, TEM, HRTEM, XRD and TPR-H2. The promotion with 8 wt.% Y (Y/Si=0.05) resulted in the highest activity and H2/CO molar ratio closer to the stoichiometric value at temperatures from 600 to 750°C. The characterization results of the yttrium promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 43 publications
5
38
0
1
Order By: Relevance
“…In our previous study we showed that Y (0.6-1.5 wt.%) increased specific surface area of Ni-DLHs, led to smaller Ni crystallites and enhanced dispersion of active sites as compared to the unpromoted catalyst [4]. Similar positive effects were reported in other Y-promoted materials tested in DRM [18,[23][24][25][26]. Moreover, Zr-modified hydrotalcites doped with yttrium (0.2-0.6 wt.%) showed good catalytic performance [18].…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…In our previous study we showed that Y (0.6-1.5 wt.%) increased specific surface area of Ni-DLHs, led to smaller Ni crystallites and enhanced dispersion of active sites as compared to the unpromoted catalyst [4]. Similar positive effects were reported in other Y-promoted materials tested in DRM [18,[23][24][25][26]. Moreover, Zr-modified hydrotalcites doped with yttrium (0.2-0.6 wt.%) showed good catalytic performance [18].…”
Section: Introductionsupporting
confidence: 70%
“…Yttrium has also been reported as a promising promoter, especially in dry reforming of methane [4,18,[23][24][25]. In our previous study we showed that Y (0.6-1.5 wt.%) increased specific surface area of Ni-DLHs, led to smaller Ni crystallites and enhanced dispersion of active sites as compared to the unpromoted catalyst [4].…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, the addition of yttrium can limit the sintering of nickel during the reaction. On the other hand, It is well known that the large nickel particle size may be favored for selective reactions that lead to carbon deposition [18,19]. As a consequence, NiO-ZrO m -YO n can limit the carbon deposition.…”
Section: Basicity Of Y-doped and Y-free Nio-zro M Catalystsmentioning
confidence: 99%
“…be favored for selective reactions that lead to carbon deposition [18,19]. As a consequence, NiO-ZrOm-YOn can limit the carbon deposition.…”
Section: Nickel Particle Size and Crystallized Phases Of Y-doped And mentioning
confidence: 99%
See 1 more Smart Citation